The Italian Labor Market : Stylized Facts, Institutions, and Directions for Reform - Prasad, Eswar (IMF Working Papers; Working Paper ;, 1998)
This paper provides a synthesis of existing and new empirical perspectives on the structure of the Italian labor market, using data at different levels of disaggregation. The analysis indicates that aggregate data mask considerable disparities in labor market outcomes across regions and demographic groups. The evolutions of sectoral wage and employment structures also point to some dimensions of labor market rigidities. A micro data set with individual data is then used to highlight key structural problems that affect labor supply and demand. The implications of these different strands of empirical analysis for the formulation and effective implementation of labor market policy are then discussed.